Early-Onset Sepsis Evaluation in Persistently Hypothermic Late Preterm and Term Infants: A Single-Center Retrospective Study - Sloane, Amy J.; Pirozzi, Justine; Benzinger, Lauren; Mattioli, Maria; Izzo, Laura; Carola, David; Solarin, Kolawole; Aghai, Zubair H. (American Journal of Perinatology, 2025)
This study aimed to evaluate outcomes and resource utilization in neonates ≥35 weeks' gestation admitted to the neonatal intensive care unit (NICU) for persistent hypothermia, and to assess the incidence of early-onset sepsis (EOS) as well as the potential benefit of using the Kaiser Permanente EOS calculator for risk stratification.This retrospective study included 161 neonates born ≥35 weeks' gestation admitted to the NICU with persistent hypothermia (core temperature <36.5°C on three separate measurements) at a tertiary care hospital between April 2017 and June 2024. Data were collected from medical records, including EOS evaluation via blood cultures, lumbar puncture, complete blood count (CBC), and C-reactive protein (CRP). The incidence of EOS was assessed, and the performance of EOS calculator was evaluated.Among 161 infants with available data, the mean gestational age was 37.9 ± 1.9 weeks, and the average birth weight was 2.72 ± 0.5 kg. There were no cases of culture-positive EOS. Thirty-eight percent of infants were low birth weight and 30% were late preterm. Isolated hypothermia without additional symptoms occurred in 64% of the infants. A blood culture was sent in 62.7% of infants, 60.1% had at least one CBC sent, 26.7% had a CRP sent, and 23.6% were treated with empiric antibiotics. More infants would have managed without blood culture and without empiric antibiotics if the EOS calculator had been used (49.7 vs. 36.0%, p = 0.01).The prevalence of EOS in persistently hypothermic infants is low despite widespread laboratory testing and empiric antibiotic use. NICU admission and laboratory workup and empiric antibiotics is probably unnecessary in persistently hypothermic infants who are otherwise well appearing. A management approach guided by EOS calculator may help to reduce evaluation and empiric antibiotics, but many persistently hypothermic late preterm and term infants will still be evaluated and treated with empiric antibiotics.
Keywords: hypothermia; sepsis; neonates